Византийские печати, найденные в Керчи и на Таманском полуострове, из собрания Н.П. Лихачева - Степанова, Е.В. (Материалы по археологии, истории и этнографии Таврии, 2007)
Что касается Керченского района, сведения относительно византийских моливдовулов очень скудны. В фондах Керченского музея-заповедника хранится лишь одна печать, которая в 2006 г. была опубликована Н.А. Алексеенко. Печать, хотя и единственная, очень интересна по своему историческому содержанию. Она датируется второй половиной X в. и принадлежит Льву, императорскому спафарию и турмарху Готии. Другой экземпляр этой печати был найден несколькими годами ранее в составе Херсонского архива печатей. The author of the article examines Byzantine seals - a source of new important information on the medieval history of Eastern Crimea and Taman peninsula after they became a part of the Byzantine Empire. The base of sphragistic data of the Kerch and Taman peninsulas was supplemented with 12 molybdoboulloses from the collection of N. P. Likhachev which are kept in State Hermitage. Seals of high-ranking officials of Byzantium (seal of John the Angel), found on this territory are of particular interest. The seal, dating back to the end of the 12th century, belonging to Theodora Comnenus, a daughter of Alexius I Comnenus, and the seal, obviously, of customs office with the inscription «For ferriage» are of great interest; A considerable number of molybdoboulloses of financial officials on the Taman peninsula, which embrace a chronological interval from the second half of the 8th till the 9th centuries, are singled out. A number of seals point to the relations of this region with Gothia, Cherson, Macedonia, and Constantinople itself; presence of seals of metropolitan officials testify to it.